(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article briefly explores the system of teaching religious enlightenment of Kazakhs in China, including the history and the system of training «Abakia madrasah» located in the Altai Territory, which is the basis of the gathering of the Kazakh intelligentsia. The same reason for the opening of madrassas among Chinese Kazakhs were socio-political states, people’s interest in religious studies and the spiritual nature of the Chinese Kazakh society of that time. And by today Kazakhs living near the border called «Chinese Kazakhs» in spiritual and political processes make small religious reports about the place and role of the madrasah «Abakia». Key words: islam, madrasah, mosque, usul Jadid, usul hadim, school.